MULTIPLICATION OF EXPLANTS IN VITRO CULTURE OF ACACIA MEARNSII DE WILD. - Piazza, Eliara Marin; Jung, Ana Paula; Felker, Roselene Marostega; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708733 The Acacia mearnsii De Wild., Popularly known as black wattle, occupies the third place among species grown in Brazil, aiming toward economic extraction of tannin, pulp production and energy coal. Within this context, this work aims to perform the in vitro multiplication of explants of Acacia mearnssi De Wild, introduced in the culture medium at 1% BAP. For step of multiplication were used as explants source nodes and hypocotyl. At all concentrations tested there was the development of axillary buds, with at least one sprout per nodal segment, and the maximum number was 3 shoots, the interaction occurring between the middle and the concentrations used. Thus, it is concluded that the composition and concentrations used were appropriate for this species as the plant growth regulator used in vitro culture, induced the appearance of adventitious roots, callus initiation, elongation and cell division.